Sudden Infant Death Syndrome - risk factors and prevention - Fabian-Danielewska, Anna; Janik-Fuks, Inga; Wawryków, Agata; Maciejewska, Martyna; Korabiusz, Katarzyna; Wilczyńska, Agnieszka; Stecko, Monika (Journal of Education, Health and Sport, 2019)
SIDS - Sudden Infant Death Syndrome is a sudden, unexpected death of an infant during sleep, which can not be justified by a medical history or post-mortem examination. This is undoubtedly one of the worst situations that young parents can encounter. Fear for child is enormous and often man tries to do everything to protect his offspring from danger, pain and illness. Unfortunately, SIDS concern healthy-growing infants, who are not suspected of any disease. The vast majority of cases occur in a baby cot, less often in the bed of parents, a pram or a car seat. It mainly concerns children up to 6 months old, but it also happens at a later age. The aim of this work is to discuss the risk factors and prevention of Sudden Infant Death Syndrome